Kemudahan Penggunaan Alat Bantu Simple Foot Elevator (SFE) dalam Perawatan Luka Kaki Diabetes - Huda, Nuh; Widayanti, Dini Mei (Jurnal Ilmiah Keperawatan STIKES Hang Tuah Surabaya, 2017)
Increasing the number of patients with DM, complications are also increasing, one of them is ulceration of the lower limbs, with or without infection and cause damage to the underlying tissue, hereinafter referred to as diabetic foot (KD) or diabetic foot wound. In the world, the number of diabetic foot patients is expected to continue to rise. Diabetic wound care also creates difficulties for the nurse. The purpose of this study is to analyze the level of ease of simple foot elevator (SFE) tools in the treatment of diabetic wounds. This type of research is quasi experimental Pre and Post Test Without Control Design by creating a prototype called SFE. This tool was then tested on 12 diabetic patient nurses with diabetic ulcer complications in the lower extremity area. The variable of this study is to measure the degree of ease of nurses in performing the treatment of Diabetic Injuries through the questionnaire. Data processing research with Mann Withney test with significance level (Î± = 0,05) or CI = 95%. The result of statistical test by using Mann-Whitney test is 0.014, the result p is less than Î±, meaning that statistically shows that the use of SFE (Simple Foot Elevator) tool is easy to be used by nurses when performing diabetic foot ulcer treatment in Room 3 Rumkital Dr. Ramelan Surabaya. The use of SFE is easy to use. So it can be recommended as one alternative tool that can be used in wound care.Keyword : Diabetes Mellitus, Diabetic Foot Wounds, SFE